Independent evidence for an association between general cognitive ability and a genetic locus for educational attainment. Issue 5 (7th May 2015) - Trampush, Joey W.; Lencz, Todd; Knowles, Emma; Davies, Gail; Guha, Saurav; Pe'er, Itsik; Liewald, David C.; Starr, John M.; Djurovic, Srdjan; Melle, Ingrid; Sundet, Kjetil; Christoforou, Andrea; et al.
Abstract : Cognitive deficits and reduced educational achievement are common in psychiatric illness; understanding the genetic basis of cognitive and educational deficits may be informative about the etiology of psychiatric disorders. A recent, large genome‐wide association study (GWAS) reported a genome‐wide significant locus for years of education, which subsequently demonstrated association to general cognitive ability (" g ") in overlapping cohorts. The current study was designed to test whether GWAS hits for educational attainment are involved in general cognitive ability in an independent, large‐scale collection of cohorts. Using cohorts in the Cognitive Genomics Consortium (COGENT; up to 20, 495 healthy individuals), we examined the relationship between g and variants associated with educational attainment. We next conducted meta‐analyses with 24, 189 individuals with neurocognitive data from the educational attainment studies, and then with 53, 188 largely independent individuals from a recent GWAS of cognition. A SNP (rs1906252) located at chromosome 6q16.1, previously associated with years of schooling, was significantly associated with g ( P = 1.47 × 10 −4 ) in COGENT. The first joint analysis of 43, 381 non‐overlapping individuals for this a priori‐ designated locus was strongly significant ( P = 4.94 × 10 −7 ), and the second joint analysis of 68, 159 non‐overlapping individuals was even more robust ( P = 1.65 × 10 −9 ). These results provide independent replication, in a large‐scale dataset, of a genetic locus associated with cognitive function and education. As sample sizes grow, cognitive GWAS will identify increasing numbers of associated loci, as has been accomplished in other polygenic quantitative traits, which may be relevant to psychiatric illness. © 2015 Wiley Periodicals, Inc.